Pengaruh Fungsi Kepemimpinan Kepala Kantor Cabang Pembantu dan Iklim Organisasi terhadap Profesionalitas Pegawai pada Kantor Cabang Pembantu Bank BJB Syariah - Handri Rahmat Ilahi; Wresni Pujiyati; Dekawati Dekawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2020)
This research focuses on studying factors that affect the professionalism of employees. Based on the leadership function of the head of the sub-branch office and the organizational climate are factors that are thought to have an influence on employee professionalism. Therefore, the study examines three variables, namely the leadership function of the head of a sub-branch office (X1), organizational climate (X2), and employee professionalism (Y). This research uses a quantitative approach, with descriptive and verification methods. The data collection technique used a questionnaire. The respondents are employees of Bank BJB Syariah, Bogor sub-branch office. The data analysis technique used regression analysis. This study found that the leadership function of the head of a sub-branch office is in the very good category. The organizational climate is in the very good category, and the professionalism of the employees of the Bank BJB Syariah sub-branch offices in the Bogor area is in the very good category. Based on the results of regression analysis, the results show that the leadership function of the head of the sub-branch office and the organizational climate either partially or simultaneously has a positive and significant effect on employee professionalism.